Macrophage-Specific Toll Like Receptor 9 (TLR9) Causes Corpus Cavernosum Dysfunction in Mice Fed a High Fat Diet. Issue 4 (16th March 2021) - Priviero, Fernanda; Calmasini, Fabiano; Dela Justina, Vanessa; Wenceslau, Camilla F.; McCarthy, Cameron G.; Webb, R. Clinton
ABSTRACT: Background: Erectile dysfunction (ED) has been shown to be related with inflammatory markers in humans. Chronic infusion of TNF-α caused ED in mice while TNF-α knockout mice exhibited improvement in the relaxation of the corpus cavernosum (CC). Aim: Since obesity triggers an inflammatory process, we aimed to investigate the hypothesis that in obesity, Toll-like receptor 9 (TLR9) activation leads to increased TNF-α levels and impairment in CC reactivity. Methods: Four-week old male C57BL6 (WT) and TLR9 mutant (TLR9MUT ) mice were fed a standard chow or high fat diet (HFD) for 12 weeks. Body weight and nonfasting blood glucose were analyzed. Contractile and relaxation responses of the CC were evaluated by electrical field stimulation and concentration response curves to phenylephrine and acetylcholine. Protein expression of nNOS, TNF-α, TNF-R1, TLR9 and MyD88 were measured by western blot. Plasma levels of TNF-α were measured by ELISA. Outcome: In obesity, impaired cavernosal relaxation is associated with the activation of the innate immune system, by increasing the production of TNF-α through the activation of TLR9 in the macrophages. RESULTS: After 12 weeks of HFD both WT and TLR9MUT mice had increased body weight and nonfasting blood glucose compared to standard chow. In the CC, acetylcholine-induced relaxation was not changed. A trend to increased contraction to phenylephrine and KCl was seen in WT HFD only. electrical field stimulation-induced relaxation of the CC was decreased in WT HFD as well as nNOS expression in the CC of WT HFD, but not in TLR9MUT HFD. In the CC, protein expression of TLR9 and MyD88 was similar in all groups. While circulating levels of TNF-α presented only a trend to increase in mice fed HFD, the CC expression of TNF-α was increased only in WT HFD mice. Clinical Translation: The innate immune system can be a target for the treatment of erectile complications in obesity. Strengths and Limitations: This is the first study demonstrating that activation of TLR9 expressed in macrophages leads to impaired cavernosal relaxation. The main limitation of the study is the lack of understanding about the source/expression of the macrophages in the cavernous tissue. Further, herein, the experiments were performed only in isolated cavernous tissue (in vitro), thus the lack of knowledge on how the TLR9 modulates the in vivo response of the erectile tissue is another limitation of this study. CONCLUSION: Our findings indicate that CC dysfunction observed in obesity is at least in part mediated by the production of TNF-α upon activation of TLR9 expressed in the macrophages.